Squalene and Sterol Carrier Protein: Structural Properties, Lipid-Binding, and Function in Cholesterol Biosynthesis - Ritter, Mary C. (1973)
Squalene and sterol carrier protein of liver plays a general role as a vehicle for cholesterol and its water-insoluble precursors; the carrier protein is essential for enzymic cholesterol synthesis. Liver microsomal enzymes contain a small amount of endogenous carrier protein, which is readily removed by washing or purification of the enzyme. Enzymic conversion to products of a cholesterol precursor·carrier protein complex is markedly faster than that for initially unbound sterol. The protomer form of the carrier protein has a molecular weight of 16,000; during sodium dodecyl sulfate gel electrophoresis one band is observed. Phospholipid facilitates the aggregation of the protomer to the oligomer form (>150,000 daltons; purified 720-fold) accompanied by the binding of cholesterol precursors to the oligomer. The carrier protein binds fatty acids as well as cholesterol precursors, suggesting that it may more generally be a lipid carrier protein with “squalene and sterol carrier protein” describing the functional aspects of the lipid carrier in cholesterol biosynthesis. Studies with several steroids and related compounds revealed that the binding sites of lipid carrier protein must contain highly specific hydrophobic and polar regions.